ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN KEUANGAN MAHASISWA FEB DI SOLO RAYA - Novita Kinsky Meliani; Suhesti Ningsih; Hadi Samanto (CV. Denasya Smart Publisher, 2025)
This research ims to determine the influence of financial literacy, lifestyle, and social media on the financial management of FEB (Faculty of Economics and Business) students in Solo Raya. The objects of this research are students of the Faculty of Economics and Business in the Solo Raya region. This research is a quantitative study. The sample was selected using accidental sampling technique, resulting in 100 respondents. This study used primary data obtained through questionnaires. The data analysis techniques in this study are validity tests, reliability tests, classical assumption tests and hypothesis testing which include multiple linear regression analysis, F test, t test, and determination coefficient test (R2). The results of the partial test study show that financial literacy, lifestyle, and social media variables have a positive and significant effect on financial management